PASCAL-based mitral valve repair in an all-comer population: acute and mid-term clinical results - Schlegel, Philipp; Crespo López, Patricia; Kreußer, Michael; Katus, Hugo; Frey, Norbert; Geis, Nicolas; Raake, Philip (ESC heart failure, 2021)
Aims We investigated short and mid-term safety and efficacy of the PASCAL system for percutaneous mitral valve repair (PMVr) in severe mitral regurgitation (MR) in an all-comer population. Methods and results In the first consecutive 41 patients undergoing PMVr using the PASCAL system in our centre, procedural success and safety were assessed. Efficacy in improving MR and functional class were evaluated. Median patient age was 74 years, 58.5% were male patients, and median European System for Cardiac Operative Risk Evaluation Score II was 5.1%. All patients suffered from severe MR with 59% functional MR, 29% degenerative MR, and 12% of mixed aetiology MR. The technical success rate was 90%, limited by four cases where PASCAL implantation was aborted due to a prohibitive mitral gradient. On average, 1.16 PASCAL devices per patient were implanted. All patients successfully implanted with a PASCAL device were discharged with MR grade ≤ 2 and 79% with MR grade ≤ 1. Mean follow-up was 8.7 ± 4.9 months. Ninety-seven per cent of patients remained at MR ≤ 2 at follow-up, which translated into a significantly improved New York Heart Association functional class as well as a significant reduction of systolic pulmonary artery pressure and brain natriuretic peptide levels. The procedure-related rate for major adverse events was 3%. Neither early nor late single-leaflet detachment was found. In one patient, air embolism occurred, resulting in modification of the PASCAL instructions for use. Conclusions Percutaneous mitral valve repair using PASCAL in a real-world, all-comer population was feasible and safe, resulting in a significant mid-term reduction of MR with persistent clinical improvement.